HASIL PENELITIAN PENGEMBANGAN MEDIA PEMBELAJARAN BUKU CERITA BERGAMBAR UNTUK MENUMBUHKAN KARAKTER SISWA KELAS 3 SD - Lusy Andriyani; Mawardi . (Institut Pendidikan Tapanuli Selatan, 2020)
This study aims to determine the development of picture story book learning media to foster the character of grade 3 elementary school students. This study uses a 4D development model with 4 stages, namely: Define, Design, Develop, and Disseminate. The research method used is a quantitative method. Data collection techniques in this study used a questionnaire. The results of the 3 validator tests (material experts, media experts and learning design experts) obtained different scores. The feasibility score obtained from material experts was 85.5% and categorized as very high, the feasibility score of the media expert was 95.5% and the category was very feasible, and from the learning design experts got a feasibility score of 75.5% categorized as feasible to use. The results showed that the development of picture story book learning media to foster the character of grade 3 elementary school students was suitable for use in learning in grade 3 elementary school.